Nuclear Transition Matrix Elements for Double-β Decay Within PHFB Model - Rath, P. K.; Chandra, Ramesh; Chaturvedi, K.; Raina, P. K. (Frontiers in Physics, 2019)
Employing the projected-Hartree-Fock-Bogoliubov (PHFB) approach, nuclear transition matrix elements (NTMEs) have been calculated to study the three complementary modes of β−β− decay, namely two neutrino β−β− (2νβ−β−) decay, neutrinoless β−β− (0νβ−β−) decay within mass mechanism and Majoron accompanied 0νβ−β− (0νβ−β−χ) decay. Reliability of HFB wave functions generated with four different parametrizations of the pairing plus multipolar type of effective two-body interaction has been ascertained by comparing a number of nuclear observables with the available experimental data. Specifically, the calculated NTMEs M(2ν) of 2νβ−β− decay have been compared with the observed data. Effects due to different parametrizations of effective two-body interactions, form factors and short-range correlations have been studied. It has also been observed that deformation plays a crucial role in the nuclear structure aspects of 0νβ−β− decay. Uncertainties in NTMEs calculated with wave functions generated with four different parametrizations of the pairing plus multipolar type of effective two-body interaction, dipole form factor and three different parametrizations of Jastrow type of short-range correlations within mechanisms involving light Majorana neutrinos, heavy Majorana neutrinos, sterile neutrinos and Majorons have been statistically estimated.